Expand \(-(3-c)(c+2(3-c))\).What is the sum of the coefficients of the expanded form?

Wsai12 Jun 9, 2021

#1**+2 **

-(3-c)(c+2(3-c))

**Hello Guest!**

- (3 - c)(c + 2(3 - c)) = - (3 - c)(c + 6 - 2c)

= - (3c + 18 - 6c - c² - 6c + 2c²)

= - c² + 9c -18

Which coefficients do you mean?

!

asinus Jun 9, 2021

#3**+2 **

I think it's -1, 9, -18.

Another cool trick you can use to find the sum of coefficients is to just plug in c as 1.

-(3-1)(1+2(3-1))

This works because the final answer in expanded form will look like xc^2 + yc + z, and if c = 1, x1^2 + y1 + z = x + y + z, which is the sum of the coefficients. :))

=^._.^=

catmg
Jun 9, 2021